1997
DOI: 10.1038/nm0297-212
|View full text |Cite
|
Sign up to set email alerts
|

Late escape from an immunodominant cytotoxic T-lymphocyte response associated with progression to AIDS

Abstract: The precise role played by HIV-specific cytotoxic T lymphocytes (CTL) in HIV infection remains controversial. Despite strong CTL responses being generated during the asymptomatic phase, the virus persists and AIDS ultimately develops. It has been argued that the virus is so variable, and the virus turnover so great that escape from CTL recognition would occur continually, but so far there is limited evidence for CTL escape. The opposing argument is that evidence for CTL escape is present but hard to find becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
239
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,033 publications
(246 citation statements)
references
References 29 publications
5
239
2
Order By: Relevance
“…In addition, some loci such as HLA-B35 (8) and -B27 (9) are individually associated with faster and slower development of AIDS, respectively. The virus escapes this CTL response (10,11), which confirms that CD8 ϩ T lymphocytes exert an immunological pressure (12). This evidence indicates a protective role of CTL in preventing and controlling HIV infection.…”
supporting
confidence: 54%
“…In addition, some loci such as HLA-B35 (8) and -B27 (9) are individually associated with faster and slower development of AIDS, respectively. The virus escapes this CTL response (10,11), which confirms that CD8 ϩ T lymphocytes exert an immunological pressure (12). This evidence indicates a protective role of CTL in preventing and controlling HIV infection.…”
supporting
confidence: 54%
“…However, virusspecific CD8 ϩ T cell immune responses are not equally effective in HIV control, as the majority of infected individuals progress to disease despite the presence of these cells. HIV is able to evade immune responses by developing mutations that mediate escape from CTL recognition (6)(7)(8)(9)(10)(11)(12). In addition, the expression of certain HLA class I molecules by HIV-infected patients, such as HLA-B*27, HLA-B*57, HLA-B*58:01, HLA-B*81:01, and HLA-A*74: 01, is associated with better clinical disease outcomes in some population settings (3,(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Moreover, among controllers with or without protective HLA class I alleles, the infection is dynamic such that loss of viral control is observed at least in a subset of individuals who were previously elite controllers. The best-studied examples of progression in elite controllers are of HLA-B*27-positive subjects in whom escape within the immunodominant Gag epitope appears to precipitate loss of viremic control (10,31). However, the mechanisms underlying the loss of viral control in previous controllers are largely undetermined, and few studies have addressed this issue.…”
mentioning
confidence: 99%
“…The rapid replication kinetics and the low-fidelity RT enzyme of HIV-1 allow a high mutation rate, which enables the virus to evade host immune surveillance. Studies with CTLs have shown that mutations, even single amino acid changes, of viral sequences that specify immunogenic epitopes can lead to escape from CD8 T-cell recognition [18][19][20][21]25], impairing the ability of the host to control infection. Little data exists however on the influence of HIV-1 antigenic variation on HLA class II-restricted CD4 T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of antigenic variation in HLA class I-restricted epitopes has been widely studied [18][19][20][21], work on the influence of HIV-1 antigenic variation on HLA class II-restricted CD4 T-cell responses has been limited, probably due to the difficulty of detecting these responses in HIV-1 infected individuals at any stage of infection. The objective of this study was to determine whether differences in the amino acid sequences of envelope glycoproteins from HIV-1 isolates of infected children would influence the ability to detect Env-specific Thelper cell responses.…”
Section: Introductionmentioning
confidence: 99%